2022
DOI: 10.3390/foods11192943
|View full text |Cite
|
Sign up to set email alerts
|

Co-Fermentation of Edible Mushroom By-Products with Soybeans Enhances Nutritional Values, Isoflavone Aglycones, and Antioxidant Capacity of Douchi Koji

Abstract: Douchi is a traditional salt-fermented soybean food with various bioactivities, such as anti-oxidation, anti-diabetes, and anti-hypertension, which are greatly affected by the activities of protease and β-glucosidase during koji production. Edible mushroom by-products are ideal ingredients for enhancing food flavor and nutritional quality due to their unique nutritional characteristics of high protein, rich amino acids, and low calories. However, there is no research on the preparation of Douchi by the mixed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It was observed that this cultivation can generate by-products such as mycelia, stipes, caps, not-commercial mushrooms, and spent mushroom substrate with a considerable content of phenolic compounds [ 5 , 35 ] Mushrooms do not have the enzymes to synthesize flavonoids, although they can absorb these compounds from the substrate or plants from which they form mycorrhizae [ 36 ]. The profile of phenolic compounds varies according to the mycorrhizae species, but in general, gallic acid is the most predominant in fermentates and dry powder produced from residues derived from the cultivation of various mushroom species together with chlorogenic, cinnamic, coumaric, and 4-hydroxybenzoic acids [ 5 , 37 , 38 , 39 ].…”
Section: Composition In Phenolic Compounds Of By-productsmentioning
confidence: 99%
“…It was observed that this cultivation can generate by-products such as mycelia, stipes, caps, not-commercial mushrooms, and spent mushroom substrate with a considerable content of phenolic compounds [ 5 , 35 ] Mushrooms do not have the enzymes to synthesize flavonoids, although they can absorb these compounds from the substrate or plants from which they form mycorrhizae [ 36 ]. The profile of phenolic compounds varies according to the mycorrhizae species, but in general, gallic acid is the most predominant in fermentates and dry powder produced from residues derived from the cultivation of various mushroom species together with chlorogenic, cinnamic, coumaric, and 4-hydroxybenzoic acids [ 5 , 37 , 38 , 39 ].…”
Section: Composition In Phenolic Compounds Of By-productsmentioning
confidence: 99%
“…In vitro A previous study revealed that douchi has an antioxidant effect via DPPH radical scavenging activity and an increase in superoxide dismutase, glutathione peroxidase, and catalase, which are known antioxidant enzymes 103,104 . Douchi also has antioxidant capacity, as measured by protease and b-glucosidase activities 105 .…”
Section: Douchimentioning
confidence: 99%